Molecules in motion: unravelling the dynamics of vascularization control in tissue engineering - Rodrigues, Francisco A. P. (2024)
Significant progress has been made in tissue engineering (TE), aiming at providing personalized solutions and overcoming the current limitations of traditional tissue and organ transplantation. 3D bioprinting has emerged as a transformative technology in the field, able to mimic key properties of the natural architecture of the native tissues. However, most successes in the area are still limited to avascular or thin tissues due to the difficulties in controlling the vascularization of the engineered tissues. To address this issue, several molecules, biomaterials, and cells with pro- and anti-angiogenic potential have been intensively investigated. Furthermore, different bioreactors capable to provide a dynamic environment for in vitro vascularization control have been also explored. The present review summarizes the main molecules and TE strategies used to promote and inhibit vascularization in TE, as well as the techniques used to deliver them. Additionally, it also discusses the current challenges in 3D bioprinting and in tissue maturation to control in vitro/in vivo vascularization. Currently, this field of investigation is of utmost importance and may open doors for the design and development of more precise and controlled vascularization strategies in TE.